Fontes Nicaenae Synodi : The Contemporary Sources for the Study of the Council of Nicaea (304-337) - Fernández, Samuel, (Contexts of Ancient and Medieval Anthropology ;, 2024)
"Fontes Nicaenae Synodi" is a sourcebook that provides the original text with an English translation and footnotes of the contemporary sources for the study of the Council of Nicaea (325). These sources are letters, canons, creeds, imperial documents, and synodal statements that deal with the theological, institutional, and disciplinary issues discussed at Nicaea - not only the "Arian" controversy. The book includes texts that are contemporary with the events, i.e., written between the beginning of the Melitian crisis (ca. 304) and the death of Constantine (337). They were passed on in Greek, Latin, and Syriac. The year 2025 will see a centenary of the synod of Nicaea (325-2025), which will be a promising scenario for discussing the Nicaean Council, a pivotal event in the formation of Western culture.